Pengembangan Kurikulum Pendidikan Agama Islam Untuk Mengatasi Bias Kognitif Dalam Pembelajaran - Eneng Humaeroh (Penerbit Widina, Widina Media Utama, 2026)
Cognitive bias refers to systematic tendencies in thinking that can interfere with learners’ understanding of instructional content and lead to irrational decision-making. In the context of Islamic Religious Education (IRE), cognitive bias has the potential to generate misconceptions that affect not only academic achievement but also religious attitudes and behaviors. This study aims to analyze the role of IRE curriculum development in minimizing cognitive bias within the learning process. The research employs a literature review method using a descriptive-narrative approach by examining books, nationally and internationally indexed journal articles, and relevant educational policy documents. The findings indicate that common forms of cognitive bias in IRE learning include confirmation bias, overconfidence, availability bias, and the Dunning-Kruger effect. An integrative, contextual, and adaptive curriculum supported by information literacy, concept clarification, value-based inquiry learning, and the strengthening of critical thinking skills has been shown to be effective in reducing the potential impact of cognitive bias. This study concludes that a systematically designed IRE curriculum grounded in students’ needs, along with teachers’ readiness to apply debiasing strategies, can foster learners who are critical, reflective, and capable of objectively evaluating and verifying religious information.ABSTRAKBias kognitif merupakan kecenderungan sistematis dalam berpikir yang dapat mengganggu pemahaman peserta didik terhadap materi ajar dan berdampak pada pengambilan keputusan yang tidak rasional. Dalam konteks Pendidikan Agama Islam (PAI), bias kognitif berpotensi menimbulkan kesalahan pemahaman keagamaan yang tidak hanya memengaruhi capaian akademik, tetapi juga sikap dan perilaku beragama. Penelitian ini bertujuan untuk menganalisis peran pengembangan kurikulum PAI dalam meminimalkan potensi bias kognitif dalam proses pembelajaran. Metode yang digunakan adalah studi literatur (library research) dengan pendekatan deskriptif-naratif melalui penelaahan buku, artikel jurnal nasional dan internasional, serta dokumen kebijakan pendidikan yang relevan. Hasil kajian menunjukkan bahwa bentuk bias kognitif yang sering muncul dalam pembelajaran PAI meliputi confirmation bias, overconfidence, availability bias, dan Dunning–Kruger effect. Pengembangan kurikulum yang integratif, kontekstual, dan adaptif, melalui penguatan literasi informasi, klarifikasi konsep, pembelajaran berbasis inkuiri nilai, serta penguatan keterampilan berpikir kritis, terbukti efektif dalam mengurangi potensi bias kognitif. Kesimpulan penelitian ini menegaskan bahwa kurikulum PAI yang dirancang secara sistematis dan berbasis kebutuhan peserta didik, disertai kesiapan guru dalam menerapkan strategi debiasing, mampu membentuk peserta didik yang kritis, reflektif, dan objektif dalam memahami serta memverifikasi informasi keagamaan.